Effects of Simultaneously Applied Short-Term Transcutaneous Electrical Nerve Stimulation and Tactile Stimulation on Memory and Affective Behaviour of Patients with Probable Alzheimer’s Disease - E. Scherder; A. Bouma; L. Steen (Behavioural Neurology)
In previous studies beneficial effects of peripheral electrical or tactile nerve stimulation were observed on memory and affective behaviour in patients with probable Alzheimer's disease. In the present study, it was investigated whether electrical and tactile stimulation applied simultaneously to Alzheimer patients would exceed the effects which were observed following treatment by each type of stimulation separately. Our data reveal that the simultaneous application of the two types of stimulation had a beneficial effect on non-verbal and verbal long-term recognition memory. In addition, patients who were treated participated more in activities of daily living, and were more interested in social contacts. In spite of these positive results, comparisons with those of previous studies suggest that a combination of electrical and tactile stimulation does not yield more effects than application of each type of stimulation separately.